Synthesis of Biodegradable Bioplastic from Xanthan Gum (XCD) Recovered from Hi-Vis Sweep Waste Generated during Well Service Operations in Bunyu Field - Dyta Silvia Mayasari; Widi Astuti; Ratna Dewi Kusumaningtyas; Dewi Selvia Fardhyanti (Universitas Negeri Semarang, 2026)
Well service operations in the oil and gas industry utilize sweep fluids based on xanthan gum (XCD), which generate high-viscosity waste with the potential to cause environmental pollution. Due to its natural polymer characteristics, XCD waste has significant potential to be utilized as a raw material for biodegradable bioplastic production. This study aims to synthesize and characterize biodegradable bioplastics derived from XCD waste generated from Hi-Vis sweep operations during well service activities in Bunyu Field. The bioplastics were prepared using the solution casting method with variations in XCD concentration (1.0–2.0%), plasticizer type (glycerol and sorbitol), and plasticizer concentration (20–40%). The resulting bioplastics were characterized through film thickness, water absorption, and biodegradation rate tests. The experimental data were further analyzed using Response Surface Methodology (RSM) based on a Central Composite Design (CCD).The results showed that increasing plasticizer concentration enhanced both water absorption capacity and film flexibility. Bioplastics plasticized with glycerol exhibited a higher biodegradation rate compared to those containing sorbitol. These findings demonstrate that XCD waste from Hi-Vis sweep operations can be effectively valorized as an environmentally friendly raw material for biodegradable bioplastic production.